Lucky in love ebook - Brown, Carolyn (Lucky Cowboys, 2009)
Book 1 of the Lucky trilogy From New York Times and USA Today-bestselling author Carolyn Brown comes a contemporary Western romance filled to the brim with sexy cowboys, gutsy heroines, and genuine down-home Texas twang. Beau Luckadeau has always been lucky at cards, lucky with cattle, and lucky with land, but he's never been lucky in love... Everything this hunky rancher touches turns to gold—except relationships. Beau hasn't got a lick of sense when it comes to women. The woman of his dreams slipped through his fingers, and he's gotten himself tied up with a gold-digger. Then spitfire Milli Torres shows up practically in his backyard. Milli can mend a fence, pull a calf, or shoot a rattlesnake between the eyes. She's come to help out at the Lazy Z Ranch, and she's horrified to learn that her nearest neighbor is the very man she hoped never to lay eyes on again. And if Beau ever figures out what really happened on that steamy Louisiana night when they first met, there'll be the devil to pay. Fans of Linda Lael Miller and Diana Palmer will thrill to this moving story of a cowboy hero who gets a second chance with the woman of his dreams. Lucky Series: Lucky in Love (Book 1) One Lucky Cowboy (Book 2) Getting Lucky (Book 3) Praise for Bestselling Contemporary Western Romances by Carolyn Brown: "An old-fashioned love story told well... A delight."—RT Book Reviews, 4 Stars "Sizzling hot and absolutely delectable."—Romance Junkies "Funny, frank, and full of heart... One more welcome example of Brown's Texas-size talent for storytelling."—USA Today Happy Ever After "Alive with humor... Another page-turning joy of a book by an engaging author."—Fresh Fiction